The Effect of Credit Risk on Profitability of Indonesian State-Owned Commercial Banks: The Intervening Role of Operating Efficiency - Chezia Rauly Simatupang; Muslimin Muslimin; Muhammad Yunus Kasim; Fera Fera (Green Publisher Indonesia, 2026)
This research explores the influence of credit risk, specifically non-performing loans (NPL), on the profitability of Indonesian state-owned commercial banks, using operational efficiency as an intervening variable. State-owned banks in Indonesia play a significant role in supporting the national economy through credit distribution, particularly to small and medium-sized enterprises (SMEs). However, rising NPL ratios present a critical challenge, impacting financial stability and profitability. The study investigates how NPLs, as a proxy for credit risk, affect profitability, with operational efficiency—measured by the operating expenses to operating income (OEOI) ratio—acting as a mediator. Using data from four state-owned banks over the period 2015–2024, the research applies path analysis and mediation tests to examine direct and indirect relationships. The findings reveal that NPL positively affects operating efficiency, which in turn negatively affects profitability (return on assets—ROA). Furthermore, operational efficiency significantly mediates the correlation between NPL and profitability. These outcomes suggest that improving operational efficiency can help diminish the negative influences of high credit risk. By integrating risk control mechanisms with operational efficiency, state-owned banks can ensure long-term profitability. This study provides practical insights for bank management in strengthening sustainable banking operations in an emerging economy.